2021
DOI: 10.3390/cryst11121531
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced X-ray Attenuating Efficiency of Silicon Dioxide Nanoparticles with Cesium Lead Bromide and 2,5-Diphenyloxazole Co-Embedded Therein

Abstract: An X-ray-attenuation-based in vivo imaging can be a promising candidate for real-time detection of cancer in an early stage due to its significantly longer penetration depth compared to currently investigated fluorescence-emission-based imaging techniques. It has recently been demonstrated that this novel concept of imaging is feasible using cesium lead bromide (CPB) quantum dots (QDs) stably embedded in silicon dioxide (SiO2) nanoparticles (NPs). However, further improvements are necessary to realize its prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“… 182 In this study, it was found that SiO 2 NPs possess potential anticancer properties against colon cancer. 183 …”
Section: Silicon Dioxide Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“… 182 In this study, it was found that SiO 2 NPs possess potential anticancer properties against colon cancer. 183 …”
Section: Silicon Dioxide Nanoparticlesmentioning
confidence: 99%
“…synthesized SiO 2 NPs conjugated with (3‐glycidyloxypropyl)trimethoxysilane (3GPS), and these NPs were characterized on the basis of size, morphology, SEM, thermogravimetric analysis, Fourier transform infrared spectroscopy (FTIR), and transmission electron microscopy (TEM) 182 . In this study, it was found that SiO 2 NPs possess potential anticancer properties against colon cancer 183 …”
Section: Silicon Dioxide Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation